Persuasive Communication in Dharma Wacana as an Effort to Build Self-Image at Pura Agung Tirta Bhuana Bekasi - Suhardi, Untung; Kinasih, Ika Yoga; Suarsa Putra, I Made Jaya Negara; Sudaria, Ketut (International Journal of Multidisciplinary Sciences, 2025)
In Hindu religious activities, Dharma Wacana must be delivered in an efficient manner in order for the public to accept the spiritual message. The Pendharma Wacana's proficiency in conveying the message is crucial to the transmission of this dharma message. However, particularly in Pura Agung Tirta Bhuana Bekasi, there aren't many Pendharma Wacana that play the role of personal branding in promoting the dissemination of Hindu doctrines. This research methodology combines a case study technique with a qualitative approach. Seven (seven) Pendharma Wacana with a variety of backgrounds. The results demonstrate that trustworthiness is increased by careful preparation, which includes mastery of appearance, practice, and substance. Congregational comprehension is facilitated by distinctive communication styles like humor, intonation, and simple language. Furthermore, their image as role models is reinforced by their traditional appearance (white attire, saput, and characteristic accessories) and their consistent application of everyday Hindu ideals. In addition to making it easier to distribute religious content, Pendharma Wacana's personal branding helps the congregation develop strong emotional ties when coaching is being provided. Their religious expertise, communication abilities, and moral character all contribute to their increased social acceptance. Particularly in urban settings, this study makes a significant contribution to the advancement of contemporary Hindu lecture techniques. In addition to enhancing the idea of religious communication, the theoretical and practical implications of the eight elements that make up Pendharma Wacana's personal branding also provide a strategic framework for the creation of flexible communal communication tactics in large cities.